Peran Mediasi Perceived Value dalam Memediasi Pengaruh Experiental Marketing terhadap Behavioral Intention (Studi pada Wisata Wahana di Kota Batu) - Mohammad Fakhruddin Mudzakkir; Iva Nurdiana Nurfarida (Jurnal Studi Manajemen dan Bisnis, 2018)
The  purpose  of  this  study  is  to  find  out  the  role  of  perceived  value  in  mediating experiential marketing influence towards  Behavioral Intention of visitors in Wisata Wahana of Batu City. The samples were 100 respondents from visitors of Eco Green Park, Jatim Park I and II. analysis technique using path analysis. The result of the study shows that experiential marketing has significant and positive influence towards perceived  value  and  Behavioral  Intention.  The  perceived  value  variable  has  been proven to be able to mediate experiential marketing influence towards the Behavioral Intention  of  visitors  significantly,  while  the  mediation  happen  is  partial,  because without the perceived value variable as mediation, the experiential marketing variable can affect the Behavioral Intention.